2018
DOI: 10.1016/j.juro.2017.12.065
|View full text |Cite
|
Sign up to set email alerts
|

WATER: A Double-Blind, Randomized, Controlled Trial of Aquablation ® vs Transurethral Resection of the Prostate in Benign Prostatic Hyperplasia

Abstract: Surgical prostate resection using Aquablation showed noninferior symptom relief compared to transurethral prostate resection but with a lower risk of sexual dysfunction. Larger prostates (50 to 80 ml) demonstrated a more pronounced superior safety and efficacy benefit. Longer term followup would help assess the clinical value of Aquablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(115 citation statements)
references
References 24 publications
3
96
0
5
Order By: Relevance
“…Aquablation is a recently commercially available technique that integrates real-time ultrasound imaging with a robotically executed surgeon-guided high-velocity waterjet to resect prostate tissue precisely [7][8][9]. In WATER, a blinded randomized trial of aquablation vs TURP in prostates with volumes of 30-80 mL, aquablation was shown to have efficacy similar to that of TURP but with a much lower risk of sexual side effects [10]. After previously reporting procedural outcomes [11], in the present paper we report 6month efficacy data from WATER II, a prospective multicentre trial of aquablation in men with symptomatic BPH and prostate volumes 80-150 mL.…”
Section: Introductionmentioning
confidence: 99%
“…Aquablation is a recently commercially available technique that integrates real-time ultrasound imaging with a robotically executed surgeon-guided high-velocity waterjet to resect prostate tissue precisely [7][8][9]. In WATER, a blinded randomized trial of aquablation vs TURP in prostates with volumes of 30-80 mL, aquablation was shown to have efficacy similar to that of TURP but with a much lower risk of sexual side effects [10]. After previously reporting procedural outcomes [11], in the present paper we report 6month efficacy data from WATER II, a prospective multicentre trial of aquablation in men with symptomatic BPH and prostate volumes 80-150 mL.…”
Section: Introductionmentioning
confidence: 99%
“…Previously a large, blinded, multicentre, randomized trial (WATER) showed that aquablation resulted in improved urinary symptom scores, similar to those observed after TURP in men with BPH and prostate volumes between 30 and 80 mL . Notable findings for aquablation included a mean operating time of 33 min for an average prostate volume of 54 mL.…”
Section: Discussionmentioning
confidence: 82%
“…Early studies have shown high levels of efficacy with low risks of sexual side effects . In the recent WATER study, a blinded randomized trial of aquablation vs TURP in 30–80‐mL prostates, aquablation had equivalent overall efficacy, with a noteworthy reduction in retrograde ejaculation compared with TURP (10% vs 36%; P < 0.001) . In a subgroup of larger (50–80‐mL) prostates, aquablation provided superior symptom‐reduction efficacy in IPSS compared with TURP.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder traction was maintained for an average of 18 h. The authors report that fulguration was available to the surgeons in this trial, but none chose to use it as they felt that balloon tamponade was an effective haemostatic mechanism. Fulguration was preferentially avoided based on the WATER trial , where it was noted that anejaculation rates were twice as large in the aquablation with fulguration compared to the Aquablation without fulguration group (16% vs 7%). The company (PROCEPT BioRobotics, Redwood City, CA, USA) even developed a novel catheter tensioning device (CTD) to assist with controlling the tension on the balloon tamponade demonstrating the old adage that ‘Necessity is the mother of Invention’.…”
mentioning
confidence: 99%
“…No functional outcome or effectiveness measures were reported. The initial WATER trial hints at possible effectiveness, but we will have to wait to see the results from this particular cohort of patients with large prostates (WATER II).…”
mentioning
confidence: 99%